ACTUAL BEHAVIORAL STRATEGY AND CONVENIENCE TOWARDS CONSUMER SATISFACTION THROUGH BRAND IMAGE UMKM IN MEDAN CITY - Bunga Aditi (RADJA PUBLIKA, 2024)
The main indicators that make MSMEs experience many losses to the point of bankruptcy, including consumer demand for the product is decreasing, then the regulations and policies issued by the government do not provide direct benefits in developing MSMEs so that they are not felt directly by the community, especially Micro, Small and Medium Enterprises (MSMEs) who have to close for a long time. The purpose of this studyreview and analyze Online Marketing Strategies and Brand Image in Reducing Bankruptcy of MSMEs in Medan City.This study uses a data analysis method using SmartPLS software. The results of the study showActual behavior has a significant effect on brand image. Brand image has a significant effect on consumer satisfaction. Brand image as an intervening variable has a significant impact in increasing the influence of Actual behavior on consumer satisfaction.